Analisis Penerapan Prinsip Bisnis Syariah Pada Hotel Berkonsep Syariah di Kota Jambi - -, Rohana (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
The focus in this research is on the Analysis of the Application of Sharia Business Principles in Hotels with Sharia Concepts in Jambi City, where as a sample there are five sharia hotels in Jambi City including: Al Fath Hotel, Matahari 1 Sharia, Diva residence Syariah, RedDoorz Syariah, Syariah Ocean. The theory used in this theory is the Principles of Sharia business (Agus Yulliawan. 2023) there are four principles (axios) that must be applied in Islamic business, namely: monotheism (Unity), balance or alignment (Equilibrium), free will (Free will), and responsibility. And also using the 2014 Ministry of Tourism and Creative Economy regulations concerning Sharia Hotel business guidelines. The type of research used is descriptive qualitative. The results of this study are that the application of Sharia Business Principles to Hotels with a Sharia concept is fairly good, what has not been fulfilled is the CSR Budget section. Meanwhile, in terms of regulations from the Ministry of Tourism and Creative Economy for the swimming pool and spa products, then for the services that have not been fulfilled, namely entertainment and sports facilities, in several sharia hotels in Jambi City. The obstacle faced in implementing the Sharia hotel business is that there are many conventional hotels in Jambi City with complete facilities, while sharia hotels still do not have the facilities owned by conventional hotels such as: Fitness Center, Sauna, Spa, entertainment and sports facilities, not yet available. varied and a large meeting room (Ballroom). All of this is of course an obstacle for sharia hotels in the city of Jambi to be able to compete with existing conventional hotels.